THE EFFECTIVENESS OF ENGLISH SONGS FROM YOUTUBE TO IMPROVE LISTENING ABILITY OF EIGHT STUDENTS OF MTS MUHAMMADIYAH 8 SIABU - Siregar, Wikanti Hartati (jurnalalfa, 2024)
The purpose of this study was to determine the effectiveness and significance of using English songs to improve the listening skills of class VIII-1 students of MTs Muhammadiyah 8 Siabu. The method in this research is the quantitative method. The subjects of this study were students of class VIII-1 MTs Muhammadiyah 8 Siabu. The sample of this study amounted to 20 students. The instruments used in this study were pre-test, treatment, post-test and interviews. The results of this study indicate that the use of English songs from YouTube is effective in improving students' listening skills. This can be seen from the results of the study showing that the average score of students' listening skills before using English songs from YouTube skills after using English songs from YouTube is 66.25 and is categorized as "good". Based on data analysis, the t-test value is higher than the table t-test (8.750>2.09), meaning that there is a significant difference. Therefore Ho is rejected and Ha is accepted, it can be said that the use of English songs is effective from YouTube in the teaching and learning process and can improve students' listening skills